solation and characterization of naphthalene utilising bacteria from Nairobi River - Budambula, Nancy; Mwachiro, E.C. (My University, 2006)
Bacteria that utilise naphthalene were isolated on minimal medium from 3 sites along the Nairobi River. Sixteen isolates were obtained, characterised and identified as Listeria sp., Aerococcus viridans, Streptococcus adjacens, Bacillus sp., Staphylococcus ltominis, Serratia liquefaciens, Kluyvera sp., Klebsiella pneumoniae pneitmoniae, Pseudomonas putida, Pseudomonas mendocina and Listonella damsella. Microbial growth was used as an indicator of naphthalene degradation. Listeria sp., A. viridans, S. adjacens, Bacillus sp., S. hominis, S. liquefaciens and P. mendocina showed heavier growth at 80 mg/I of naphthalene as compared to no naphthalene. The 16 isolates were generally resistant to ampicillin and lincomycin but sensitive to nalidixic acid, norfloxacin and minocycline. Bacillus sp (NR34) showed the highest level of resistance to antibiotics. Plasmids ranging between 1 kb and 3.5 kb were isolated from Pseltdontonas putida. The Kluyvera sp. was shown to carry plasmids that ranged from 2 kb to 55 kb.
Keywords: Bacteria; naphthalene; Nairobi River; isolates